Effectiveness of computed tomography perfusion imaging in stroke management - Cviková, Martina; Haršány, Michal; Vinklárek, Jan; Štefela, Jakub; Fojtová, Iva; Mikulík, Robert (Frontiers in Neurology, 2024)
Guidelines do not support the use of computed tomography perfusion (CTP) unless it is used to diagnose penumbra in extended time window treatment. This study aimed to define the yield of CTP for stroke diagnosis beyond penumbra imaging in the hyperacute phase (0-6 hours) and extended time window (6-24 hours).All consecutive patients with acute onset of symptoms within a 24-hour window underwent CTP. The diagnostic value of CTP was calculated against the clinical and radiological diagnosis of stroke. CTP was positive in the presence of core or penumbra on RAPID. Clinical diagnoses were discharge diagnoses of stroke. Radiological diagnosis was established if early ischemic changes (ASPECTs < 10) on baseline CT scan, acute infarction on follow-up imaging, or symptomatic occlusion on baseline CT angiography was present.Between Nov/2018-Nov/2019, 585 consecutive patients with acute neurological deficit were scanned with multimodal CT imaging; 500 (85%) were included: 274 (55%) within the hyperacute phase, 153 (31%) had radiological diagnoses of stroke, and 122 (24%) clinical diagnoses of stroke. CTP was positive only in patients with confirmed stroke (positive predictive value and specificity 100%). When CTP was negative, 43% had a stroke mimic. Patients with stroke mimics were younger (6617 vs. 7313) and had lower National Institutes of Health Stroke Scale (median 0; IQR 0-2 vs. median 4; IQR 2-6) compared to patients with CTP negative stroke.In stroke management, CTP is most useful if it is positive because in our study, it always meant brain ischemia. Positive CTP should prompt adequate stroke management without delay. If CTP is negative, both stroke and non-stroke diagnoses need to be considered.